2017
DOI: 10.1371/journal.ppat.1006530
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the CD40-CD40L pathway augments T-helper cell responses and improves control of Mycobacterium tuberculosis infection

Abstract: Mycobacterium tuberculosis (Mtb) impairs dendritic cell (DC) functions and induces suboptimal antigen-specific CD4 T cell immune responses that are poorly protective. Mucosal T-helper cells producing IFN-γ (Th1) and IL-17 (Th17) are important for protecting against tuberculosis (TB), but the mechanisms by which DCs generate antigen-specific T-helper responses during Mtb infection are not well defined. We previously reported that Mtb impairs CD40 expression on DCs and restricts Th1 and Th17 responses. We now de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 57 publications
8
73
0
Order By: Relevance
“…Our results indicate that both IFN-γ single-positive and IFN-γ+IL-17+ double-positive cells emerge soon after Mtb infection and persist for several weeks, thus likely contributing to controlling Mtb infection during LTBI. These data support and extend previous studies in mice (50, 55, 56) and in macaques (28, 53) suggesting that balanced Th 1 and Th 17 responses are associated with enhanced immunity to TB. Future studies that selectively deplete IL-17 or IFN-γ + CD4 T cells in the context of LTBI or vaccination in macaques will provide more direct evidence for the role of these cells in LTBI.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that both IFN-γ single-positive and IFN-γ+IL-17+ double-positive cells emerge soon after Mtb infection and persist for several weeks, thus likely contributing to controlling Mtb infection during LTBI. These data support and extend previous studies in mice (50, 55, 56) and in macaques (28, 53) suggesting that balanced Th 1 and Th 17 responses are associated with enhanced immunity to TB. Future studies that selectively deplete IL-17 or IFN-γ + CD4 T cells in the context of LTBI or vaccination in macaques will provide more direct evidence for the role of these cells in LTBI.…”
Section: Discussionsupporting
confidence: 91%
“…HIV and Mtb coinfected human DCs showed reduced expression of costimulatory molecules CD40, CD80 and CD86 as well as pro-inflammatory IL-6, IL-1b and TNF-a, resulting in an impairment to stimulate IFN-c production by CD4 + T cells [155]. In line with these findings, it was recently demonstrated that CD40dependent co-stimulation of DCs was crucial to initiate protective Th17 responses in TB [156]. Qualitative changes in cytokine expression involving reduced Th1 responses have previously been demonstrated in PBMCs from TB/HIV co-infected patients [157,158].…”
Section: Tb/hiv Co-infectionmentioning
confidence: 71%
“…Mucosal administration of DCs has been utilized to assess early antigen-specific T cell responses to mycobacteria in the lungs of mice (12), and antigen-loaded DCs have previously been shown to confer protection against Mtb challenge (9, 1315). Therefore, we used a tractable DC intratracheal instillation model to assess antigen-specific CD4 T cell responses in vivo following transfer of BCG or BCGΔ hip1 -infected DCs, or control uninfected DCs, into the lungs of mice.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our studies suggest that deleting BCG hip1 alone, or in concert with deleting additional immune evasion genes, is a feasible approach to enhance DC functions for the rational improvement of BCG as a vaccine. A growing number of studies indicate that vaccination through the mucosal route induces robust antigen-specific responses that confer better protection at mucosal surfaces, such as the lung, relative to parenteral routes (9, 13, 14, 4348). Using an intratracheal DC installation model, we observed that transfer of DCs infected with BCGΔ hip1 into mouse lungs more effectively activated CD4 T cells, induced higher numbers of antigen-specific mucosal CD4 T cells secreting IFN-γ, IL-2, TNF-α, and IL-17 in vivo, and led to enhanced Mtb control after challenge compared to transfer of BCG-DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation